Authenticity and versioning of learning objects using the digital signature infrastructure of Costa Rica - Alpizar-Chacón, Isaac; Chacón-Rivas, Mario (LACLO 2016, 2016)
There are a large number of educational resources available on the Internet through different repositories. However, authenticity methods of learning objects has not been widely adopted by repositories, making it difficult to verify the authors of the content. To solve this problem, our goal is to aid users and authors of learning objects to have a trusted verification of authenticity and versioning of learning objects by applying digital signatures into the lifecycle of learning objects. In our propose, after a learning object is uploaded to a repository, the author presents his/her digital certificate, a special LOM record is created with the information from the author’s certificate, and then it is signed to prove its authenticity. The signature is produced using digital certificates issued by the digital signature infrastructure of Costa Rica, which guarantees legal binding and trust over time. We hope to propose a generic framework than can be implemented in any repository.
© © 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works
Keywords: Learning Objects; Digital signatures; Authenticity; Learning Object Repositories; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Library and information science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education